Antiretroviral treatment‐based cost saving interventions may offset expenses for new patients and earlier treatment start. Issue 3 (31st October 2013) - Angeletti, C; Pezzotti, P; Antinori, A; Mammone, A; Navarra, A; Orchi, N; Lorenzini, P; Mecozzi, A; Ammassari, A; Murachelli, S; Ippolito, G; Girardi, E
<x xml:space="preserve">Abstract</x> Objectives Combination antiretroviral therapy (cART) has become the main driver of total costs of caring for persons living with HIV (PLHIV). The present study estimated the short/medium‐term cost trends in response to the recent evolution of national guidelines and regional therapeutic protocols for cART in Italy. Methods We developed a deterministic mathematical model that was calibrated using epidemic data for Lazio, a region located in central Italy with about six million inhabitants. Results In the Base Case Scenario, the estimated number of PLHIV in the Lazio region increased over the period 2012–2016 from 14 414 to 17 179. Over the same period, the average projected annual cost for treating the HIV‐infected population was €147.0 million. An earlier cART initiation resulted in a rise of 2.3% in the average estimated annual cost, whereas an increase from 27% to 50% in the proportion of naïve subjects starting cART with a nonnucleoside reverse transcriptase inhibitor (NNRTI)‐based regimen resulted in a reduction of 0.3%. Simplification strategies based on NNRTIs co‐formulated in a single tablet regimen and protease inhibitor/ritonavir‐boosted monotherapy produced an overall reduction in average annual costs of 1.5%. A further average saving of 3.3% resulted from the introduction of generic antiretroviral drugs. Conclusions In the medium term, cost saving interventions could finance the increase in costs resulting from the inertial growth in the number of patients requiring treatment and from the earlier treatment initiation recommended in recent guidelines.